Internal and external barriers to effective supply chain management implementation in malaysian manufacturing companies: a priority list based on varying demographic perspectives - Anis, Azilah; Islam, Rafikul; Hashim, Hizam; Abdul Rahim, Abdul Rahman (2025)
Identifying and prioritizing internal and external barriers to supply chain management (SCM) is crucial, especially in a developing country context like Malaysia, where challenges often stem from limited awareness and unclear objectives within the supply chain network. This study thus aims to compare the ranking of various demographic groups in relation to the internal and external barriers experienced by Malaysian manufacturing companies, a topic that has received minimal attention. The identified lists of internal and external barriers are prioritised using the Analytic Hierarchy Process (AHP) from ten respondents with wide-ranging experience in SCM. The ranking of the respondents from different races, age groups, education levels, employment types, work experience, and designations suggests significant variations between these groups in terms of the ranking of internal and external barriers. The findings of this research provide significant information to company managers who desire to implement SCM in a multi-cultural setting such as Malaysia. The onus is on these managers to be cautious in developing a strategic plan for its effective SCM implementation and also in designing programs to overcome SCM obstacles.